2014
DOI: 10.1097/brs.0000000000000259
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous Resorption of Lumbar Disc Herniation Is Less Likely When Modic Changes Are Present

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 35 publications
2
59
1
2
Order By: Relevance
“…IDH volume decreased from 1433.89 ± 525.49 mm 3 to 1002.01 ± 593.95 mm 3 , resulting in an average resorption rate of 27.25 ± 32.97%, and 20 patients presented resorption rates of ≥50% [10]. While modic change was not recognized as a predictive factor of resorption in this study, a 2014 study by Shan et al reported that whereas 35 of 85 patients in the modic change group (of whom the majority were of Type 2) did not show much difference in IDH size, the group with no modic change displayed significant decrease [32]. Iwabuchi et al purported that resorption factors could be identified on T1- and T2-weighted MRIs, with high signal intensity of IDH areas in T1- and T2-weighted MRIs in the nonregression group [33].…”
Section: Discussionmentioning
confidence: 71%
“…IDH volume decreased from 1433.89 ± 525.49 mm 3 to 1002.01 ± 593.95 mm 3 , resulting in an average resorption rate of 27.25 ± 32.97%, and 20 patients presented resorption rates of ≥50% [10]. While modic change was not recognized as a predictive factor of resorption in this study, a 2014 study by Shan et al reported that whereas 35 of 85 patients in the modic change group (of whom the majority were of Type 2) did not show much difference in IDH size, the group with no modic change displayed significant decrease [32]. Iwabuchi et al purported that resorption factors could be identified on T1- and T2-weighted MRIs, with high signal intensity of IDH areas in T1- and T2-weighted MRIs in the nonregression group [33].…”
Section: Discussionmentioning
confidence: 71%
“…; Shan et al. ). Other studies have argued that any potential positive correlation between cartilage endplate herniations and pain and clinical symptoms will be confounded by the inflammatory effect of the nucleus material in the extrusion (Joe et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Shan et al. ). It has been suggested that non‐virulent anaerobic bacteria can infect the disc at the time of herniation.…”
Section: Discussionmentioning
confidence: 98%
“…New research results have shown that in patients with disc herniations the ingrowth of capillaries and inflammatory mechanisms may be important ingredients of the development of pain and MC in the involved spinal structures [14]. Additional observations point to a possible association between the high proportion of hyaline cartilage in the herniated disc mass and the development of MC in the adjacent segments [15]. As the bony endplates normally have a rich supply of small free nerve endings, degenerative developments and inflammation can trigger a localized inflammatory pain pattern [5,16].…”
Section: Etiology and Painmentioning
confidence: 97%